Strategy Development of Small Qualification Company in Construction Service Business Competition - Adi Utomo; Ervina Ahyudanari (Budapest International Research and Critics University, 2021)
This study will develop a strategy model for a small qualifying company in the field of Construction Services using the David model. In principle, there are three steps in David's model, namely the input stage, matching stage, and decision stage. The Analytical Hierarchy Process (AHP) is used to determine the weight of the internal and external factors of the strategy and the Quantitative Strategic Planning Matrix (QSPM) to determine the chosen alternative strategy. From the results of the External Factor Evaluation (EFE), Internal Factor Evaluation (IFE) and Competitive Profile Matrix (CPM) matrix at the input stage, the Strength-Weakness-Opportunity-Threat (SWOT) matrix, Strategic Position and Action Evaluation (SPACE), Grand Strategy (GS) at the matching stage which produces several alternative strategy proposals. Then the decision stage using the Quantitative Strategic Planning Matrix (QSPM) is selected the alternative strategy with the highest score. From the selected alternative strategy recommendations, a strategy model is then made with a new Business Model Canvas (BMC). The results of the research are expected to create an appropriate strategy to be used as a reference for small qualified Construction Service Companies to win the competition and be able to move up to the qualifications above (medium). Thus, the composition of small companies in Indonesia is increasingly ideal hence a good business competition climate will be created for small qualified construction services, besides that, a new strategy is also obtained for PT. ABC-U.